2022
DOI: 10.2174/1570162x19666211206094709
|View full text |Cite
|
Sign up to set email alerts
|

HIV Stigma Reduction Interventions Among Health Care Providers and Students in Different Countries: A Systematic Review

Abstract: Background: Health care providers’ stigmatizing attitudes are obstacles to patients’ well-being and quality of life. Dealing with HIV-related stigma and understanding the impact of feasible interventions on reducing stigmatizing attitudes among health care providers are considered important strategies to improve the quality of HIV care, patient-provider relationships, and provide supportive and safe care services. Objectives: The aim of this study was to systematically review interventions to reduce HIV-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Although less common, successful interventions have also taken place at the facility level. A systematic review of HIV stigma-reduction interventions highlight that interventions have been efficacious in reducing HIV-related stigma among healthcare providers [50]. A study by Pollack et al .…”
Section: Mitigating Stigma To Improve Uptake Of Hiv Servicesmentioning
confidence: 99%
“…Although less common, successful interventions have also taken place at the facility level. A systematic review of HIV stigma-reduction interventions highlight that interventions have been efficacious in reducing HIV-related stigma among healthcare providers [50]. A study by Pollack et al .…”
Section: Mitigating Stigma To Improve Uptake Of Hiv Servicesmentioning
confidence: 99%
“…[42][43][44] Peer support, peer navigation, and harm reduction services are all evidence-based strategies for reducing-or overcoming-stigma against substance use, HIV, and homelessness in healthcare settings. [45][46][47] Expanding the availability of harm reduction services within and beyond traditional healthcare settings may be an important step toward resolving these long-standing barriers to care. The global opioid settlement between US states and Teva, Allergan, CVS, Walgreens, and Walmart may provide a new opportunity for US jurisdictions to accomplish this.…”
Section: Discussionmentioning
confidence: 99%
“…This same situation could be evidenced in the studies by Barrington et al and Feyissa et al, who reported that patients were afraid to go to clinics where the PLHIV care units were clearly labeled as "HIV centres" and allowed the patients to be identified like HIV positive by other people only for the fact to go to these centres [18,19] Discrimination by healthcare personnel is part of structural stigma, but this review considered it a separate entity. This kind of discrimination may include denial of services, dehumanizing treatment, or violation of confidentiality, which is facilitated by drivers such as lack of knowledge of the pathology, its mode of transmission and treatment, as well as fear of contagion [50][51][52][53][54]. In the quantitative studies included in this review, it was observed that the behaviors perceived by PLWH, coming from healthcare workers, were mainly negative labels, cynical questions, delay in care, refusal of care, and dissemination of serological status without authorization [21,22].…”
Section: N Discussionmentioning
confidence: 99%